Effect of grape seed extract on the quality of local meat product (basturma) during storage - FADHIL, Yaman Saad (Food Science and Technology, 2023)
Basturma is an Iraqi meat product produced to preserve meat in Iraq and manufactured from beef, fat, salt, and other spices. The goal of this research was to evaluate the impact of adding grape seed flour (GSF) in several doses (0, 1, 2, and 4%) on the local Iraqi meat product (basturma) stored at room temperature for 14 days. The proximate composition (moisture, crude fat, and crude protein) and microbiological properties (total plate count and coliform count) were investigated. In general, the applications of different concentrations of GSF showed significant differences in the moisture values throughout the storage period, and higher significant differences in the total bacteria count and coliform count have been noticed in all the treatments compared with the control treatment from the first day till the end of storage period. This study has demonstrated that GSF has the capability to be applied as a food ingredient in basturma.